The energy cultures framework: Exploring the role of norms, practices and material culture in shaping energy behaviour in New Zealand. (May 2015) - Stephenson, Janet; Barton, Barry; Carrington, Gerry; Doering, Adam; Ford, Rebecca; Hopkins, Debbie; Lawson, Rob; McCarthy, Alaric; Rees, David; Scott, Michelle; Thorsnes, Paul; Walton, Sara; et al.
Abstract: The energy cultures framework was developed in 2009 to support interdisciplinary investigation into energy behaviour in New Zealand. In this paper, we discuss the framework in light of 5 years of empirical application and conceptual development. The concept of culture is helpful in seeking to better understand energy behaviour because it conveys how behaviours are embedded within the physical and social contexts of everyday life, and how they are both repetitive and heterogeneous. The framework suggests that the energy culture of a given subject (e.g. an individual, a household, a business, a sector) can be studied by examining the interrelationships between their norms, practices and material culture, and how these, in turn, are shaped by external influences. We discuss the key theoretical influences of the framework, and how the core concepts of the framework have evolved as we have applied them in different research situations. We then illustrate how we have applied the framework to a range of topics and sectors, and how it has been used to support interdisciplinary research, in identifying clusters of energy cultures, in examining energy cultures at different scales and in different sectors, and to inform policy development.